1983
DOI: 10.1111/j.1469-7998.1983.tb05071.x
|View full text |Cite
|
Sign up to set email alerts
|

Jet propulsion in salps (Tunicata: Thaliacea)

Abstract: This paper describes the locomotion of salps by jet propulsion, from a combination of measurements of chamber pressures, static thrust, and electromyographic activity, with kinematic records of free‐swimming and tethered salps. From such measurements, estimates are made of the thrust exerted, the drag incurred, and the work performed by single salps, and by chains of linked individuals. It is concluded that salp jet propulsion is a more economical process than is jet propulsion in other animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
4

Year Published

1987
1987
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 11 publications
(12 reference statements)
1
46
4
Order By: Relevance
“…For aggregate forms, kinematic measurements may still occasionally underestimate volume flow rates. Bone and Trueman (1983) found that instantaneous velocities of individuals in an aggregate chain were smoother due to the coordinated swimming of individuals in the chain. Processing of additional fluid due to continuous forward swimming might produce even higher filtration rate than those presented here.…”
Section: Comparison With Other Methods and Broader Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For aggregate forms, kinematic measurements may still occasionally underestimate volume flow rates. Bone and Trueman (1983) found that instantaneous velocities of individuals in an aggregate chain were smoother due to the coordinated swimming of individuals in the chain. Processing of additional fluid due to continuous forward swimming might produce even higher filtration rate than those presented here.…”
Section: Comparison With Other Methods and Broader Applicationsmentioning
confidence: 99%
“…2, Fig.3 (Bone and Trueman 1983), lateral regions of the test are thin, possibly allowing for greater articulation at these points. Generally speaking, Cyclosalpa sp.…”
Section: Morphology Kinematic Trade-offs and Filtration Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to other swimming modes, jet propulsion is considered an inefficient means of locomotion, which may explain why it is not more common (Alexander 2003, Biewener 2003. However, among the jet-propelled creatures, it has been suggested that salp swimming is the most economical (Bone and Trueman 1983). A pulsed jet, as opposed to continuous jet emission, may improve hydrodynamic efficiency because the wake rolls up into a series of vortex rings that interact to create additional thrust , Madin 1990, Daniel 1985, Weihs 1977.…”
Section: Morphology and Movementmentioning
confidence: 99%
“…During swimming, the muscle bands contract against the tunic to reduce the body volume and refilling is achieved due to elastic recoil of the tunic (Bone and Trueman 1983).…”
Section: Morphology Kinematic Trade-offs and Filtration Ratesmentioning
confidence: 99%